Integrating Health and Economic Empowerment for Older Adults through Butterfly Pea Cultivation and Processing in Patianrowo Village: Pemberdayaan Lansia Desa Patianrowo melalui Budidaya dan Pengolahan Bunga Telang sebagai Integrasi Kesehatan dan Ekonomi - Rachma Nurhayati; Asih Imulda Hari Purwani; Mardiana Prasetyani Putri (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Older adults in Desa Patianrowo face interrelated health and economic challenges, characterized by a high prevalence of degenerative diseases such as hypertension and diabetes mellitus, along with limited economic independence. Although participation in the Bina Keluarga Lansia (BKL) program is relatively high, existing empowerment initiatives have not yet optimally integrated health improvement and economic strengthening based on local potential. This study reports the implementation of the TELADAN Lansia Program, a community-based service initiative designed to integrate health education and economic empowerment through the utilization of butterfly pea (Clitoria ternatea). The program involved 20 older adults and was implemented using a participatory approach in collaboration with BKL cadres and village stakeholders. Key activities included education on degenerative disease management, training on butterfly pea cultivation and processing, community-based enterprise development, and basic marketing and product branding. Program outcomes were assessed using structured pre–post evaluations to capture changes in participants’ knowledge, skills, and productive capacities. The implementation of the program resulted in improved health literacy, enhanced technical skills in cultivation and processing, and increased capacity to market locally based products. In addition, the program led to the establishment of older adult business groups, productive cultivation plots, value-added products, and digital marketing channels. Importantly, the TELADAN Lansia Program establishes a sustainable empowerment model integrated with local BKL cadres, supporting long-term continuity and offering potential for replication in communities with similar characteristics.